MODELING THE PROBLEM OF FORCED OSCILLATIONS OF A DAM-PLATE WITH CONSTANT AND VARIABLE STIFFNESS, TAKING INTO ACCOUNT THE VISCOELASTIC PROPERTIES OF THE MATERIAL AND HYDRODYNAMIC WATER PRESSURES - A. A.Tukhtabaev; M. M. Juraboev (American Journals Publishing, 2022)
In this article highlights of modeling the problem of forced oscillations of a dam-plate with constant and variable stiffness, taking into account the viscoelastic properties of the material and hydrodynamic water pressures.
Keywords: modeling, forced oscillations, dam-plate, stiffness, viscoelastic properties